Pendampingan Hukum Pemberdayaan Usaha Mikro Dan Pengembangan Bumdes Di Desa Blumbungan, Pamekasan - Wilda Prihatiningtyas; Radian Salman; Indria Wahyuni (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Partners in this community service are Blumbungan village community, Larangan District, Pamekasan Regency, East Java. Socio-economic and cultural conditions of the community as well as the activities of the Blumbungan village community are heavily influenced by socio-religious activities, including the existence of youth organizations, mosque youth, “PKK”, recitation groups, farmer groups, and the development of small/home industries (cassava chips, making cigarettes, furniture, pillar making, tofu production). The existence of this small/household industry has positive impact on increasing the income of the Blumbungan community, although there are still obstacles in practice. The problems that have been inventoried, include: (1) Lack of understanding of legal aspects in business management, (2) Lack of knowledge about marketing methods and product packaging, (3) Lack of access to capital business for WUB (New Entrepreneurs), and (4) The direction and development of Village-Owned Enterprises has not yet been determined. The method of the activities includes preparation, counselling, mentoring, and evaluation. The results and conclusions of this community service activity are: (1) Increasing knowledge of the legal basis, function, and role of BUMDes for partners, as evidenced by the results of the distributed questionnaires. (2) Village regulations regarding BUMDes, AD-ART, and the Roadmap of BUMDES Blumbungan Sejahtera are important components in the development of BUMDes. So it must be completed as part of the output in this assistance. (3) In addition to regulations, product development to be managed by BUMDes is also important. In the next mentoring, it will be focused on developing packaging systems and promoting typical Village products both offline and online. (4) With the strengthening of BUMDes as legal entities as regulated in the Village Law after the Employment Creation Law and PP BUMDes, it is easier for BUMDes to gain access to capital.